College Management System - Deshmukh Sangram Pandit,; Chavan Pruthviraj Subhash,; Autkar Chaitanya Prakash,; Prof. Jondhale D.R, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The College Management System (CMS) is a comprehensive full-stack web application designed to automate and streamline various academic and administrative operations within an educational institution. The primary objective of the system is to efficiently manage student, faculty, and course-related data while reducing manual work and improving accuracy, accessibility, and transparency. In traditional college administration, record-keeping for student admissions, attendance, examinations, results, and fee payments is often handled manually or through disparate systems, leading to inefficiency, redundancy, and data inconsistency. The proposed system addresses these issues by providing an integrated platform that connects students, faculty, and administrators through a unified digital interface. The CMS enables role-based access control, allowing different levels of system interaction — administrators can manage user accounts, departments, and courses; faculty members can mark attendance, upload grades, and post notices; students can view timetables, results, attendance records, and pay fees online. Additionally, the system provides automated report generation for academic performance, fee collection, and attendance analysis, thereby aiding decision-making and institutional monitoring. Technically, the system is developed using a full-stack architecture, where the frontend is implemented with React.js for responsive user interaction, the backend is powered by Node.js and Express.js to handle server logic and RESTful APIs, and the database is managed using PostgreSQL or MongoDB to ensure data consistency and security. The application supports JWT-based authentication for secure user sessions and is containerized with Docker for easy deployment. The proposed College Management System thus serves as an efficient, scalable, and user-friendly platform that minimizes paperwork, enhances data reliability, and improves communication among all stakeholders. By digitizing core academic processes, it contributes to better resource utilization and establishes a foundation for future integration with emerging technologies such as cloud computing and AI-based analytics.
Keywords: College Management System; Full-Stack Web Application; Automation; React.js; Node.js; Database Management; Attendance; Results; Fees Management; Academic Administration